RETRACTED OF: Analisis Wacana Kritis Program Blak-Blakan Edisi Keempat Jawa Pos Radar Semeru Tv - Choliq, Abdul; Sidkin Ali, Muhammad (IAIN Madura, 2023)
Following careful and considered review of the article entitled “Analisis Wacana Kritis Program Blak-Blakan Edisi Keempat Jawa Pos Radar Semeru TV” Published in the Meyarsa: Ilmu Komunikasi dan Dakwah Vol. 4 No. 1 (2023), by Abdul Choliq and Muhammad Sidkin Ali lecturer at the Universitas Islam Negeri KH Achmad Siddiq Jember, Indonesia. This article has been retracted at the request of Author. The author has published in the ARKANA: Jurnal Komunikasi dan Media: DOI: https://doi.org/10.62022/arkana.v2i01.3380 https://ojs.unsiq.ac.id/index.php/arkana/article/view/3380 One of the conditions of submission of a paper for publication is that authors declare explicitly that their work is original and has not appeared in a publication elsewhere. Re-use of any data should be appropriately cited. As such this article represents a severe abuse of the scientific publishing system. The scientific community takes a very strong view on this matter and apologies are offered to readers of the journal that this was not detected during the submission process. The document and its content have been removed from Meyarsa: Jurnal Ilmu Komunikasi dan Dakwah, and reasonable effort should be made to remove all references to this articles.